Leadership development through online gaming - Tinnawat Nuangjumnonga; Hitoshi Mitomo (International Telecommunications Society (ITS), 2012)
The relationship between leadership development and multiplayer online battle arena games (MOBA) are examined using two popular games of this genre: Defense of The Ancients (DOTA) and Heroes of Newerth (HON). Similar existing research notably includes IBM's Leadership in Games and at Work: Implication for the Enterprise of Massively Multiplayer Online Role-Playing Games published in 2007, positively concluding the contribution online games have towards leadership development. Close-ended surveys created based on Fred Fiedler's contingency model (1967) and Kurt Lewin's leadership model (1939) were distributed in Thailand both in written and online formats. The targeted respondent demographic is unemployed Thai game players 13 years old or above. Survey content determined the respondent's leadership style (authoritarian, democratic or laissez-faire) and game role (carry, support or ganker). Multinomial logistic regression and factor analyses determined that the 3197 eligible surveys collected shows a relation between MOBA games and leadership development. Based on the findings, it is concluded that those who are characterized as the game role carry are more likely to have the authoritarian leadership style and less likely to have laissez-faire leadership style. Those who are characterized as the game roles support and ganker are more likely to have the democratic leadership style and less likely to have authoritarian and laissez-faire leadership styles. Other demographic data such as age, income and education level are found to be statistically insignificant in influencing leadership development. The conclusions presented impacts the current available literature, which tends to present a comparatively negative view relevant to online games and individual behavior. Potential game development based on research findings may aid in the improvement of individuals' leadership capabilities.
Keywords: 330; leadership style; behavior; link; online game; multiplayer online battle arena; MOBA; action real-time strategy; ARTS